Shadow Economy In The Prism Of Economic Security: Current Conditions And Trends In Georgia - Kakhaber Tsimintia (Research Retrieval and Academic Letters, 2024)
The shadow economy distorts indicators of economic growth, national wealth formation, income distribution, increases property differentiation of the population, contributes to the growth and deepening of poverty, deforms the structure of the economy, criminalizes economic activity and society in general, thereby hindering the sustainable and safe socio-economic development of the country. At the same time, it distorts the real picture of economic development, contributes to the formation of negative parameters of economic security. It has a special impact on such a component of economic security as sustainable development, as it violates the stability of the elements of the economic system, increasing threats to economic security.